Enchantment eaudiobook Awakening wonder in an anxious age. - May, Katherine (Books on Tape, 2023)
#1 NATIONAL BESTSELLER “When I tell you that I dogeared almost every page in this book, I'm telling God's honest truth. I didn't know how much I needed someone else to validate what I was going through. The sense that I had lost my curiosity, my imagination, my ability to make meaning.” – NPR Morning Edition host Rachel Martin "Such a teacher for every single person who is trying to live closer to who they were born to be and not who the world tamed them to be.” – New York Times bestselling author Glennon Doyle on We Can Do Hard Things “I love Katherine May’s new book, Enchantment .…It’s a beautiful offering of light, truth and charm in these strange, dark times.” – New York Times bestselling author Anne Lamott   “Katherine May gave so many of us language and vision for the long communal ‘wintering’ of the last years. Welcome this beautiful meditation for the time we've now entered. I cannot imagine a more gracious companion. This book is a gift.” – New York Times bestselling author Krista Tippett “Gentle inspiration for those who feel exhausted or helpless… May shows how paying deliberate attention to what’s around us can surprise us with insights and reveal new connections that deepen our appreciation for the world.” – Washington Post From the New York Times –bestselling author of Wintering , an invitation to rediscover the feelings of awe and wonder available to us all Many of us feel trapped in a grind of constant change: rolling news cycles, the chatter of social media, our families split along partisan lines. We feel fearful and tired, on edge in our bodies, not quite knowing what has us perpetually depleted. For Katherine May, this low hum of fatigue and anxiety made her wonder what she was missing. Could there be a different way to relate to the world, one that would allow her to feel more rested and at ease, even as seismic changes unfold on the planet? Might there be a way for all of us to move through life with curiosity and tenderness, sensitized to the subtle magic all around?   In Enchantment , May invites the reader to come with her on a journey to reawaken our innate sense of wonder and awe. With humor, candor, and warmth, she shares stories of her own struggles with work, family, and the aftereffects of pandemic, particularly feelings of overwhelm as the world rushes to reopen. Craving a different way to live, May begins to explore the restorative properties of the natural world, moving through the elements of earth, water, fire, and air and identifying the quiet traces of magic that can be found only when we look for them. Through deliberate attention and ritual, she unearths the potency and nourishment that come from quiet reconnection with our immediate environment. Blending lyricism and storytelling, sensitivity and empathy, Enchantment invites each of us to open the door to human experience in all its sensual complexity, and to find the beauty waiting for us there.